2017
DOI: 10.3329/akmmcj.v6i2.31572
|View full text |Cite
|
Sign up to set email alerts
|

Goldsmith Workers (GSWs): A Skilled Job & Status of Illness

Abstract: Background: This study was conducted among the goldsmith workers of different goldsmith's workshops located Islampur of Dhaka city to find out respiratory illness among them. `Methodology: It was a descriptive cross sectional study. By purposive sampling a total of 120 goldsmith workers were interviewed about respiratory problems using questionnaire and checklist.Result: The study revealed out of 120 respondents 5% were illiterate, 40% had education upto Primary level and 55% respondents had education at secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
2
0
0
Order By: Relevance
“…In the current study, common NCD risk behaviors identi ed were smoking (70.0%) and alcohol consumption (50.0%). Another study in Bangladesh also reported a higher proportion (58.3%) of smokers among the goldsmith workers [17]. Similar scenario of death by CVD (55.0%) among the deceased goldsmith workers in the present study may be explained by the existence of NCD risk behaviors, which are the established risk factors for CVD [18,19].…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, common NCD risk behaviors identi ed were smoking (70.0%) and alcohol consumption (50.0%). Another study in Bangladesh also reported a higher proportion (58.3%) of smokers among the goldsmith workers [17]. Similar scenario of death by CVD (55.0%) among the deceased goldsmith workers in the present study may be explained by the existence of NCD risk behaviors, which are the established risk factors for CVD [18,19].…”
Section: Discussionsupporting
confidence: 82%
“…Another study in Bangladesh also reported a higher proportion (58.3%) of smokers among the goldsmiths. 17 Similar scenario of death by CVD (60.0%) among the deceased goldsmiths in the present study may be explained by the existence of NCD risk behaviors, which are the established risk factors for CVD. 18,19 Some limitations need to be considered before interpreting the results of this study.…”
Section: Discussionsupporting
confidence: 77%